1996
DOI: 10.1128/iai.64.3.905-912.1996
|View full text |Cite
|
Sign up to set email alerts
|

Surface localization of Helicobacter pylori urease and a heat shock protein homolog requires bacterial autolysis

Abstract: Helicobacter pylori is a gram-negative bacterium which causes chronic gastritis and is associated with peptic ulcer disease, gastric carcinoma, and gastric lymphoma. The bacterium is characterized by potent urease activity, thought to be located on the outer membrane, which is essential for survival at low pH. The purpose of the present study was to investigate mechanisms whereby urease and HspB, a GroEL homolog, become surface associated in vitro. Urease, HspB, and catalase were located almost exclusively wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
2
9

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(204 citation statements)
references
References 59 publications
12
181
2
9
Order By: Relevance
“…Based on our present and previous results [15], GroEL-like protein is located in the soluble cell fractions, but also found in the membrane fraction of A. actinomycetemcomitans. This is similar to the GroEL localization in Helicobacter pylori [25]. DnaK-like protein is located intracellularly in A. actinomycetemcomitans [15], Borrelia burgdorferi [26], and Escherichia coli, in which, additionally, a subpopulation of DnaK-like protein may be membrane-associated [27].…”
Section: Discussionsupporting
confidence: 75%
“…Based on our present and previous results [15], GroEL-like protein is located in the soluble cell fractions, but also found in the membrane fraction of A. actinomycetemcomitans. This is similar to the GroEL localization in Helicobacter pylori [25]. DnaK-like protein is located intracellularly in A. actinomycetemcomitans [15], Borrelia burgdorferi [26], and Escherichia coli, in which, additionally, a subpopulation of DnaK-like protein may be membrane-associated [27].…”
Section: Discussionsupporting
confidence: 75%
“…Wilson and his group [14,15] showed that surface associated material (SAM) from A. actinomycetemcomitans contained the GroEL-like protein and released it extracellularly in periodontal lesion. In H. pylori, HspB (GroEL homologue) is released by bacterial autolysis and becomes adsorbed to the surface of intact bacteria in vitro, and this mechanism also seems to be present in vivo when human gastric biopsies are examined [16,17]. On the other hand, Vanet and Labigne [18] concluded that secretion of HspB did not occur by a programmed autolysis process but by a speci¢c and selective mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Urease gene clusters also encode accessory genes, in addition to these structural genes, which are required for the de novo synthesis of active urease (Beenken et al, 2004). In Helicobacter pylori, urease is expressed at very high levels, and a shift to an acidic pH may result in a significant increase in the level of ure operon mRNA (Phadnis et al, 1996). In other bacteria, the urease activity is regulated in response to environmental changes, such as changes in pH, urea and nitrogen availability, and to growth phase (Burne & Chen, 2000).…”
Section: Increased Transcripts Of Urease Genesmentioning
confidence: 99%